Head trauma in a child with Sturge-Weber Syndrome overlapping Klippel-Trenaunay syndrome - Kostic, Aleksandar; Tošić, Tatijana; Mitic, Radisav; Radisavljević, Miša; Zivkovic, Slavko; Milosevic, Predrag; Stanojevic, Bojan (Acta medicae Medianae, 2021)
Abstract Here we present a case of a 10-year-old girl, who was diagnosed with SWS after she was born. The history of seizures and transient right-sided hemiparesis dates from the period of neonates. Port-wine stains of the face and on right hand and foot were present as from the birth of the child which may suggest overlapping with KTS. After a mild head trauma some hour after, vomiting, aphasia, and hemiplegia occurred. The patient was admitted to the Clinic for Neurosurgery and after observation commenced on symptomatic and antiepileptic therapy. Within the following 24 hours, aphasia resolved and hemiplegia turned into mild hemiparesis. As the neurological status improved and the patient felt better, after two more days of observation, the child was discharged from the hospital.